Ustavnopravni okvir referenduma u Republici Hrvatskoj : trenutno stanje i budući izazovi - Blagojević, Anita (Array, 2019)
The paper analyses the bacis characteristics of the fundamental and the most applicable form of direct democracy – referendum, and the basic characteristics of the existing constitutional framework of referendum in the Republic of Croatia. According to the Constitution of the Republic of Croatia there is one case of a mandatory referendum (entering into alliances with other states or of dissolution thereof), and in other cases referendum is facultative. Having in mind the previous practice of referendum in Croatia, the special emphasis in the paper is on the special form of referendum which is introduced in Croatian legal framework with the Revision of the Constitution in 2000. The introduction of the citizen-initiated referendum in a solution that is according to conditions of its application unknown to developed democracies has shown that one institute that can and should have a positive impact on the development od democray and of democratic political culture can simultaneously jeopardize the foundations of modern democracy. In this context, the aim of this paper is to point to the shortcomings of the constitutional framework of referendum in Croatia, and to propose some solutions that will minimize possibility of abusing of direct democractic decision-making.